Color determination in tomato epicarp using Computer Vision System during ripening - Padrón Pereira, Carlos Alberto (2025)
The evolution of color in tomatoes samples, during ripening under refrigeration or at room temperature, was studied by Computer Vision System (CVS). CVS consisted in a lighted stage, a CCD digital camera and a computer (Laptop), all calibrated. The digital processing of images was performed with the Adobe® Photoshop® CS3 Extended software, with which averaged images on L*, a* and b* coordinates were obtained. The proceeding tested, using CVS, allowed to study the variations of color during the ripening of tomatoes from images, by means of rectangular coordinates (L*, a*, b*). The ratio a*/b* and polar coordinates (c*, ho), showing statistically significant differences between samples determined (p<0,05).